Upaya Peningkatan Pengetahuan Masyarakat Dalam Penanganan Limbah Shuttlecock - Nadya Perdana Noerhaliza (Journal of Empowerment Community, 2026)
Shuttlecock waste accumulation from the industry could be damaging to nature. It is necessary to inform society about shuttlecock waste hazards that are difficult to biodegrade due to the feathers’ composition. Briquettes product becomes an alternative solution for reducing waste. The purpose of community engagement is to enhance public knowledge of shuttlecock waste management. The method used in the activity is public education that conducts outreach-based pre-test and post-test. The implementation of activities is located in a shuttlecock craftsman’s business house. A total of twenty-six respondents were present with worker status in the business house. The result of community engagement showed that 57.69% asserted shuttlecock waste could be made into other products, while 42.31% stated it could be reprocessed. Public knowledge of processing shuttlecock waste into briquettes is still relatively new, leading to an increase from 73.08% who reported never having heard the term ‘briquette’, to 80.77% stated that shuttlecock waste could be converted into briquettes. It is expected that improvement in knowledge will increase the economic value of shuttlecock waste, rather than selling it to a waste collector.